ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA DALAM MENYELESAIKAN SOAL CERITA OPERASI BENTUK ALJABAR - Robiatul Maghfiroh; Siti Khabibah; Gunanto Amintoko (Discovery : Jurnal Ilmu Pengetahuan, 2021)
This research aims to describe the problem solving skills of students in grade VIII LIPS BI and the factors that cause or affect students have low, moderate, and high problem solving abilities. This research is a qualitative descriptive study. The subjects in this study were 19 students of Grade VIII LIPS BI SMP Nurul Jadid Paiton Probolinggo. The instruments in this study are test and interview instruments. The data collection techniques in this study are test and interview methods. While, the data analysis techniques in this study are data reduction, data presentation and drawing conclusions. The results showed that there were 6 students with high problem solving skills, 12 students who had moderate problem solving skills, and there was only one student with low problem solving skills. The polya stage that is difficult for students to do in the problem solving skills test is the second polya step, which is at the stage of making a problem solving plan. While the contributing factor to the problem-solving skills of grade VIII students is a lack of appreciation for math lessons, students lack interest in math lessons and students dislike mathematics